The Dynamics of Cultural Identity Through the Use of English in Surabaya Postgraduate Student Environment: Dinamika Identitas Budaya Melalui Penggunaan Bahasa Inggris Pada Lingkungan Mahasiswa Pascasarjana Surabaya - Lauhil Fatihah, Lauhil Fatihah; Rasyid Fahmi Suroso (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In an increasingly globalized higher education environment, students often face demands to demonstrate competence in English as a form of intellectual capability and professionalism. The use of English among graduate students not only serves as a means of communication, both in everyday life and academically, but also influences the way they form and negotiate cultural identities. Some students feel that the use of English gives them access to global networks and increases social prestige, but on the other hand, they also face a dilemma between maintaining local cultural expressions, so the use of English becomes a symbolic space where students' cultural identities are exchanged, negotiated, and sometimes contested. This study aims to find out how the use of English can shape the cultural identity of postgraduate students in Surabaya. This research is an interpretative qualitative research and was conducted at two universities in Surabaya, namely Airlangga University and Sepuluh November Institute of Technology. Data collection techniques used in this research are participatory observation, document study, and in-depth interviews. The data analysis technique used in this research is an interpretative approach and uses a thematic analysis model. The findings show that graduate students are not passive in accepting foreign cultural influences, but rather actively negotiate and shape their identities through language use.